2021
DOI: 10.1109/access.2021.3116613
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Air Implementation of NOMA: New Experiments and Future Directions

Abstract: Non-orthogonal multiple access (NOMA) is widely recognized to increase the number of users and enhance the spectral efficiency in fifth-generation (5G) wireless networks and beyond. NOMA is still in the theoretical analysis and simulation phases and fewer experimental works are reported to date. In this paper, we design and implement NOMA in software-defined radio, and evaluate its performance. This includes the real-time realization of the key components of NOMA, i.e., superposition and successive interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Therefore, the practical systems take their values from finite alphabet inputs such as a M-level quadrature-amplitude modulation (M-QAM) constellation. In this regard, once a baseband transceiver is implemented, it has been shown that the imperfect SIC cannot be modeled only by a coefficient, and NOMA networks have a degradation of error performance (bit error rate, BER) for both downlink [26], [27] and uplink [27], [28] scenarios. These studies led other researchers to investigate the BER performance of NOMA systems with finite alphabet inputs to reflect their practical implementations.…”
Section: A Related Work and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the practical systems take their values from finite alphabet inputs such as a M-level quadrature-amplitude modulation (M-QAM) constellation. In this regard, once a baseband transceiver is implemented, it has been shown that the imperfect SIC cannot be modeled only by a coefficient, and NOMA networks have a degradation of error performance (bit error rate, BER) for both downlink [26], [27] and uplink [27], [28] scenarios. These studies led other researchers to investigate the BER performance of NOMA systems with finite alphabet inputs to reflect their practical implementations.…”
Section: A Related Work and Motivationmentioning
confidence: 99%
“…By substituting the PDF of the ith maximum ( 16) into (54), the MGF of γ i is given as Finally, as defined in (26), we put s=− g sin 2 θ into MGF (D.3), the bit error probability is derived as (27), so the proof is completed.…”
Section: Appendix D Proof Of Eq (27)mentioning
confidence: 99%
“…At the S, the messages of users are combined in an SC information signal with different power levels according to the users' channel gain 1 and the R receives this information signal in the first phase. Thus, the received information signal by the R node is given as…”
Section: System Modelmentioning
confidence: 99%
“…Non-orthogonal multiple access (NOMA) is widely renowned for increasing the number of users and improving spectral efficiency in next-generation wireless networks [1]. Besides, NOMA can be easily integrated with other physical layer schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The primary methods for SISO‐NOMA are successive interference cancelation (SIC) at the receiver and SC at the transmitter 7 . NOMA faces several challenges that must be addressed for its practical implementation and deployment in wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%